Effects of refraction and axial length on the development and progression of diabetic retinopathy - M.M. Bikbov; O.I. Orenburkina; A.E. Babushkin; A.A. Fakhretdinova (РМЖ "Клиническая офтальмология")
M.M. Bikbov, O.I. Orenburkina, A.E. Babushkin, A.A. Fakhretdinova Ufa Research Institute of Eye Diseases, Ufa, Russian Federation Eye disorders have a special place in diabetes since visual impairment has a significant effect on the quality of life. Therefore, determining risk factors and prognostic criteria for disease course are essential for developing strategies for early prevention of diabetic retinopathy (DR). This paper addresses studies on various aspects of DR in patients with myopia. It was demonstrated that DR arises, develops, and progresses in different ways under various axial lengths (AL). Thus, many authors report that DR barely occurs in high myopia. Some of them account for this phenomenon for poor blood circulation in a long myopic eye. Others refer to a significantly lower vascular endothelial growth factor (VEGF) concentration in longer eyes or eyes with myopic refraction. The third authors argue a focal disintegration of retinal pigment epithelium to eliminate metabolic end products through the choroid and sclera. As a result, neither acidosis nor venous congestion develops, and end othelial barrier function remains unaffected Keywords: diabetic retinopathy, myopia, axial length, vascular endothelial growth factor, emmetropia, hyperopia, diabetes. For citation: Bikbov M.M., Orenburkina O.I., Babushkin A.E., Fakhretdinova A.A. Effects of refraction and axial length on the development and progression of diabetic retinopathy. Russian Journal of Clinical Ophthalmology. 2021;21(4):205–209 (in Russ.). DOI: 10.32364/2311-7729-2021-21-4-205-209.